If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + 16 = 9x + 9 Reorder the terms: 16 + 8x = 9x + 9 Reorder the terms: 16 + 8x = 9 + 9x Solving 16 + 8x = 9 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. 16 + 8x + -9x = 9 + 9x + -9x Combine like terms: 8x + -9x = -1x 16 + -1x = 9 + 9x + -9x Combine like terms: 9x + -9x = 0 16 + -1x = 9 + 0 16 + -1x = 9 Add '-16' to each side of the equation. 16 + -16 + -1x = 9 + -16 Combine like terms: 16 + -16 = 0 0 + -1x = 9 + -16 -1x = 9 + -16 Combine like terms: 9 + -16 = -7 -1x = -7 Divide each side by '-1'. x = 7 Simplifying x = 7
| C(m)=0.15m+0.95 | | 6y-4=y+6 | | 4(3x-2)=2(6x+9) | | P-17=67 | | X+-5x+3=-5 | | .16(x-36)=.83 | | 7x-4x=4x-2 | | 10+3j=31 | | 2.3y+1.2=2.12whatisy | | 4x(2x-1)(3x-5)=0 | | 7x+9-2x=11-12x-13 | | (x-4)(3x+8)=0 | | 8n-8=32 | | 3x+12-5x=19-15x+13x-7 | | 8x+15=19whatisx | | x^2+12y+36=10 | | 0-7x=7 | | 4x^4-25x^2+36=0 | | 15n^2-27n-6= | | x(x-8)=33 | | 7w=49 | | n^2-4n=11 | | 12x-2=4x-20-2 | | 2x^2+4x=1 | | x^2+6p+9=4 | | 75-(3x+13)=3(x+9)+x | | 3x^4-4x^2+11=0 | | 5x-2+78=14x+13 | | 2x+19=21 | | 187=19+(13-x) | | a+5=23 | | 14x+13+78+5x-2=90 |